Make, share, review, remix: Unpacking the impact of the internet on contemporary creativity. (December 2019) - Literat, Ioana
This article advances a holistic framework that aims to facilitate a better understanding of the nuanced impact of the internet on contemporary creative participation. Functioning simultaneously as the context, locus, and medium for creative activity, the internet affects each stage in the life cycle of a creative product – creation, distribution, interpretation, and remix. In addition, this influence is felt in a wide range of creative products: off-line and online, professional and vernacular. Previous research has not examined these different processes and types of creative output in conversation with each other; by advancing an integrative analytical approach and synthesizing research from multiple domains, this work attempts to address this gap. As a way to illuminate this impact and demonstrate the value of the proposed framework, the article applies this framework to three case studies: a work of off-line art ( The Artist Is Present ), online art ( Moon ), and online nonart or vernacular online creativity (Pepe the Frog memes). This analysis facilitates a deeper understanding of these interrelated processes, attends to the complex ways in which new media blurs the borders between those categorizations, and discusses the potential implications of these complex contemporary dynamics.